2015
DOI: 10.1007/s11306-015-0830-7
|View full text |Cite
|
Sign up to set email alerts
|

Statistical treatment of 2D NMR COSY spectra in metabolomics: data preparation, clustering-based evaluation of the Metabolomic Informative Content and comparison with 1H-NMR

Abstract: Compared with the widely used 1 H-NMR spectroscopy, two-dimensional NMR experiments provide more sophisticated spectra which should facilitate the identification of relevant spectral zones or biomarkers in metabolomics. This paper focuses on 1 H-1 H COrrelation SpectroscopY (COSY) spectral data. In spite of longer inherent acquisition times, it is commonly accepted by users (biologists, healthcare professionals) that the introduction of an additional dimension probably represents a huge qualitative step for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Indeed, two or more metabolites contribute to one bucket in the 1D spectra because of signal overlap, while 2D NMR resolves this ambiguity. A similar conclusion was recently reached by Fé raud et al, who demonstrated through multivariate approaches that 2D COSY spectra provided a higher level of clustering and were more informative from the statistical point of view [11].…”
Section: D Nmr To Facilitate the Discovery Of Biomarkerssupporting
confidence: 80%
“…Indeed, two or more metabolites contribute to one bucket in the 1D spectra because of signal overlap, while 2D NMR resolves this ambiguity. A similar conclusion was recently reached by Fé raud et al, who demonstrated through multivariate approaches that 2D COSY spectra provided a higher level of clustering and were more informative from the statistical point of view [11].…”
Section: D Nmr To Facilitate the Discovery Of Biomarkerssupporting
confidence: 80%
“…These criteria are derived from unsupervised as well as supervised chemometric tools. They are gathered under the Metabolomic Informative Content (MIC) concept [13] and include inertia measures, PCA, clustering and PLS-DA related criteria. The inertia analysis decomposes the total variance into two complementary parts: the variance between the groups and the variance within the groups of observations.…”
Section: Quality Criteria For Pepsnmr Evaluationmentioning
confidence: 99%
“…The inertia analysis decomposes the total variance into two complementary parts: the variance between the groups and the variance within the groups of observations. For the clustering, the (adjusted) Rand indexes measure the true class recovery efficiency and should be maximised while the Dunn and Davies-Bouldin indexes measure the clustering homogeneity and they have to be respectively maximised and minimised (formula details can be found in Féraud et al [13]). PLS-DA builds a latent structure with Latent Variables (LV) to extract the variance components from the data but instead of maximising the spectral data matrix variance as does PCA, it maximises the variance of both the spectral data matrix (the regressors) and the class labels (the response) and their correlation.…”
Section: Quality Criteria For Pepsnmr Evaluationmentioning
confidence: 99%
“…Several signals, for instance peaks in 1 H-NMR, can overlap, move together and/ or be associated to a same molecule. So, an idea would be to apply L-sOPLS on 2D-NMR spectra (COSY for instance Feraud et al 2015) or to take into account groups of features instead of individual features as inputs of the sparse algorithms. Methods like Group-LASSO, Sparse-Group-LASSO or Overlay-Group-LASSO (Friedman et al 2010) could then be tested in this context.…”
Section: Conclusion and Further Workmentioning
confidence: 99%